Determining factors associated with breastfeeding and complementary feeding practices in rural Southern Benin - Bodjrènou, Fifali Sam Ulrich; Amoussa Hounkpatin, Waliou; Termote, Céline; Dato, Geoffroy; Savy, Mathilde (Wiley, 2021)
This study aimed at characterizing breastfeeding and complementary feeding practices in a food-insecure area of Benin and identifying factors associated with these practices. A cross-sectional study was conducted in the districts of Bopa and Houéyogbé among n = 360 mother–child pairs. Children aged 0–17 months were considered. Socioeconomic characteristics among children and mothers, Breastfeeding on demand, Breastfeeding frequency during children illness, and Positioning and Attachment of children while breastfeeding were assessed using semi-structured interviews and observations. Qualitative 24-hr recalls were administered to mothers to compute WHO recommended complementary feeding practices indicators namely minimum dietary diversity (MDD), minimum meal frequency (MMF), and minimum acceptable diet (MAD) among 6–17 months old children (n = 232).